Heightened connectivity between the ventral striatum and medial prefrontal cortex as a biomarker for stress-related psychopathology: understanding interactive effects of early and more recent stress. Issue 11 (18th December 2017) - Hanson, Jamie L.; Knodt, Annchen R.; Brigidi, Bartholomew D.; Hariri, Ahmad R.
Abstract : Background: The experience of childhood maltreatment is a significant risk factor for the development of depression. This risk is particularly heightened after exposure to additional, more contemporaneous stress. While behavioral evidence exists for this relation, little is known about biological correlates of these stress interactions. Identifying such correlates may provide biomarkers of risk for later depression. Methods: Here, we leverage behavioral, experiential, and neuroimaging data from the Duke Neurogenetics Study to identify potential biomarkers of stress exposure. Based on the past research, we were specifically interested in reward-related connectivity and the interaction of early and more recent stress. We examined psychophysiological interactions between the ventral striatum and other brain regions in relation to these stress variables, as well as measures of internalizing symptomatology ( n = 926, participant age range = 18–22 years of age). Results: We found relatively increased reward-related functional connectivity between the left ventral striatum and the medial prefrontal cortex in individuals exposed to greater levels of childhood maltreatment who also experienced greater levels of recent life stress ( β = 0.199, p < 0.005). This pattern of functional connectivity was further associated with elevated symptoms of depression ( β = 0.089, p = 0.006). Furthermore, using a moderated mediation framework, we demonstrate that this functional connectivity provides a biological link between cumulative stress exposure and internalizing symptomatology. Conclusions: These findings suggest a novel biomarker linking cumulative stress exposure with the later experience of depressive symptoms. Our results are discussed in the context of past research examining stress exposure in relation to depression.